Evasão nos cursos a distância: curso de extensão TV na Escola e os desafios de hoje - Neves, Yára Pereira da Costa e Silva (2006)
The distance Education in the teacher s formation and the introduction of the technology of information and communication is the educative innovator example in the global world. That research about the run away of the course in school and the nowadays challenges is characterized as the distance formation destined to the teachers, coordinators and directors of public schools of the world s public net, with the objective of favour the necessary base to the Technologies of Information and Communication utilization, in Special TV and video. This work had as aim to investigate the causes that took the frequenter teacher to run away from the course, once in Alagoas as the other states, there were a meaningful number of ran away. We look for area s references and subsidies to increase the quality of EAD, especially the extension course of TV in school and nowadays challenges. The utilized methodology was the study of a case, based in many sources of evidences, as documentation, consultations, interviews and questionnaires to the data collecting. The realized research involved the bibliographical data research, data collecting, to compute and data analysis. The obtained results demonstrate that the causes of the run away is related with the personal origin problems, substructure problems and problems with the pedagogic support, being the timeless for the activities excess the principal factor of the run away, taking us to rethink about the existence of the social structures that place between the education and the whole society. The research identified the causes of the run away is the context of the EAD, contributing as source of the informative knowledge that allow the decisions made and joined to the futures editions of the course offered to the teachers in work.